Pengaruh Learning Management Sistem terhadap Motivasi dan Tingkat Kepuasan Mahasiswa pada Masa Pandemik Covid-19 - Murcahyanto, Hary (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of learning management systems on student motivation and satisfaction levels during the covid-19 pandemic. The research method used is quantitative research with an associative approach. The research subjects were 60 students. The research technique used simple random sampling with data collection using questionnaire techniques. The results showed a positive and significant influence between the learning management system (LMS) and student learning motivation. Based on significant testing obtained t count (4.382) > t table (1.67155) on Y1 (learning motivation) means Ho1 is rejected and Ha1 is accepted. The results showed a positive and significant influence between the learning management system (LMS) on the level of student satisfaction. Based on significant testing, t count (5.406) > t table (1.67155) means Ho1 is rejected and Ha1 is accepted. The conclusion of this study is that learning using learning management system (LMS) has a significant effect on student motivation and satisfaction level. Keywords: Covid-19, Learning Management System, Learning Motivation, Satisfaction Level